2020
DOI: 10.3762/bjnano.11.119
|View full text |Cite
|
Sign up to set email alerts
|

Atomic defect classification of the H–Si(100) surface through multi-mode scanning probe microscopy

Abstract: The combination of scanning tunnelling microscopy (STM) and non-contact atomic force microscopy (nc-AFM) allows enhanced extraction and correlation of properties not readily available via a single imaging mode. We demonstrate this through the characterization and classification of several commonly found defects of the hydrogen-terminated silicon (100)-2 × 1 surface (H–Si(100)-2 × 1) by using six unique imaging modes. The H–Si surface was chosen as it provides a promising platform for the development of atom sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 94 publications
(171 reference statements)
0
32
1
Order By: Relevance
“…While we use a height reference defined by these STM setpoints, previous work has estimated this to correspond to an absolute tip-sample distance of ∼700 pm as established by Rashidi et al 18 where they defined z = 0 as a point where noticeable changes in tip-structure from surface contact occurred. It is also found that the absolute tip-sample distance can vary slightly (∼100 pm) due to different apex functionalizations, 54 tip geometries, and surface dopant profiles. Thus, we stick with the easily accessible STM set-point to enable easy reproduction of our results.…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…While we use a height reference defined by these STM setpoints, previous work has estimated this to correspond to an absolute tip-sample distance of ∼700 pm as established by Rashidi et al 18 where they defined z = 0 as a point where noticeable changes in tip-structure from surface contact occurred. It is also found that the absolute tip-sample distance can vary slightly (∼100 pm) due to different apex functionalizations, 54 tip geometries, and surface dopant profiles. Thus, we stick with the easily accessible STM set-point to enable easy reproduction of our results.…”
Section: Methodsmentioning
confidence: 94%
“…88 Further in situ conditioning was done via controlled tip contacts with hydrogen desorbed patches of silicon until it returned characteristics corresponding to a Si terminated tip. 25,54 DB structures were created via controlled bias pulses. 20,23,89 The bias ranges for each set of measurements refer to the sample bias (V S ) and were chosen to probe as great a bias window as possible while trying to prevent any unwanted tip changes due to high tunneling current through the valence and conduction band of the crystal.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it has been reported that the passivation of semiconducting materials, which removes surface dangling bonds and significantly reduces surface reactivity, may also provide a sufficiently insulating layer for an efficient decoupling of molecular structures from the substrate influence. Among such surfaces, hydrogen-passivated Si(001):H [ 22 23 ], Si(111):H [ 24 ], and Ge(001):H [ 25 28 ] surfaces are most commonly mentioned. Iron phthalocyanines (FePc) have been studied on Si(111):H [ 24 ] and it was concluded that the molecules are weakly coupled to the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Our methodological approach builds upon the general philosophy of using machine learning to handle data analysis challenges in Scanning Probe Microscopy (SPM) [46][47][48][49] and the specic use of deep learning Convolutional Neural Networks (CNN) 50 to recognize features in high-resolution SPM images. Recent examples include conditioning of SPM tips, 51 identication of defects with STM 52,53 and nanostructures with AFM, 54 and making molecular structure predictions from AFM images. 55 However, to the best of our knowledge, no earlier studies have applied machine learning to SPM at solid-liquid interfaces.…”
mentioning
confidence: 99%